Sutured Descemet Membrane Endothelial Keratoplasty in Patients With Complex Anatomy or Difficulty Positioning. Issue 3 (12th March 2023) - Li, Gavin; Shekhawat, Nakul S.; Eghrari, Allen O.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: In Descemet membrane endothelial keratoplasty (DMEK), some patients cannot adhere to postoperative positioning requirements or lack anatomic support for a gas bubble in the anterior chamber. We describe a suturing technique that stabilizes the graft postoperatively without tearing or tenting it. Methods: One to two 10-0 nylon sutures with a spatulated needle are used to secure DMEK grafts. Tied with minimal tension, the sutures traverse the corneal stroma at a steep, almost perpendicular angle and approach the graft from the limbus at an angle tangential to the circular graft to prevent vaulting the tissue off the central cornea. We report preoperative and postoperative best spectacle-corrected visual acuity, corneal pachymetry, and anterior segment optical coherence tomography confirming graft attachment in 3 patients. Results: In case 1 (aphakia, postvitrectomy, and positioning difficulty), pachymetry decreased from 637 μm preoperatively to 495 μm and best spectacle-corrected visual acuity improved from 20/70 to 20/50 at postoperative week 1. In case 2 (aphakia, limited follow-up, and medication adherence), pachymetry decreased from 1106 μm preoperatively to 783 μm at postoperative month 1. In case 3 (tube shunt and loss of gas bubble at 2 hours), slit-lamp examination at postoperative day 1 showed corneal clearing and graft attachment. Pachymetry decreased from over 795 μm preoperatively to 582 μm at postoperative month 1. Anterior segment optical coherence tomography confirmed graft attachment in all patients. Conclusions: Single or opposing tangentially oriented sutures can be safely applied to secure DMEK grafts postoperatively in challenging cases.